Power-Efficiency-Dissipation Relations in Linear Thermodynamics - Proesmans, Karel; Cleuren, Bart; Van den Broeck, Christian (Physical review letters, 2016)
We derive general relations between the maximum power, maximum efficiency, and minimum dissipation regimes from linear irreversible thermodynamics. The relations simplify further in the presence of a particular symmetry of the Onsager matrix, which can be derived from detailed balance. The results are illustrated on a periodically driven system and a three-terminal device subject to an external magnetic field.